Pregnancy outcome in Non-cirrhotic portal hypertension - M. R., Sandya; K., Manjula S.; Ancy, Sr. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To study the maternal and fetal outcome of non-cirrhotic portal hypertension (NCPH) in pregnancy. Methods: We retrospectively analyzed ten women with the diagnosis of NCPH in pregnancy. The study was done at St John’s Medical College Hospital Bangalore, Karnataka from January 2012 - January 2016. All the necessary data was obtained by record review. Results: The mean age of the pregnant woman was 25.5 years. Among 10 women with the diagnosis of NCPH 4 had Non-cirrhotic portal fibrosis (NCPF) and 6 had Extrahepatic portal venous obstruction (EHPVO). Six patients were diagnosed with NCPH prior to pregnancy; while among the remaining 4 patients, 1 had variceal bleed and the other 3 manifested with splenomegaly during pregnancy which led to the diagnosis of NCPH. All these 4 patients were successfully managed with beta blockers alone without any surgical intervention during pregnancy. Thrombocytopenia and splenomegaly were the most common clinical manifestations which were observed in all 10 patients. Severe thrombocytopenia (platelet <50,000 cells/mm3) was seen in 7 patients who received platelet transfusion. Six (60%) of patients had vaginal delivery, the other 4 underwent cesarean section due to meconium stained liquor and fetal distress in early labor. Hence cesarean delivery was reserved only for obstetric indication. Postpartum hemorrhage was seen in 2 patients managed conservatively, one patient on 3rd postoperative day developed ascites and pleural effusion requiring pleural tapping and diuretics with successful recovery. There was no maternal mortality during the study period. The fetal/neonatal outcome was good in the present study with 90% of babies with good APGAR score, whereas 1 preterm neonate developed HIE stage 2 requiring prolonged NICU stay. The overall pregnancy outcome was good in the present study. Conclusions: Pregnancies can be allowed and managed successfully in patients with NCPH.